Research on the effect of uncertain rewards on impulsive purchase intention of blind box products - Zhang, Yi; Zhou, Hang; Qin, Jian (Frontiers in Behavioral Neuroscience, 2022)
Since 2019, China has gradually set off a “blind box” boom, and young groups have quickly become the main force in buying blind box, promoting the continuous development of blind box industry. Previous studies have shown that uncertainty in events with positive prospects can play a more positive effect than certainty. However, how does uncertainty affect consumers’ emotion and cognition and trigger subsequent consumption behavior? In order to clarify the internal mechanism of this process, this paper takes blind box as the research object and constructs the mechanism model of perceived uncertainty on consumers’ impulsive purchase intention based on SOR theory. In addition, the variable of curiosity and the variable of perceived luck are introduced according to the information gap theory and optimism theory. The results show that the perceived uncertainty positively influences the impulsive purchase intention of consumers, and curiosity plays a partially mediating role in it. Moreover, perceived luck positively moderates the effect of perceived uncertainty on impulsive purchase intention. The research has important guiding significance for future enterprises to use blind box sales model for marketing.